The Effects of a School Policing Program on Crime, Discipline, and Disorder: A Quasi-Experimental Evaluation - Zhang, Gary (American journal of criminal justice, 2019)
This study analyzes the impacts of school-based law enforcement officers on school crime, disciplinary actions, and disciplinary problems in 238 middle and high schools in West Virginia using a non-equivalent groups design and three years of data. Propensity score weights are utilized to reduce selection biases resulting from non-random group assignment in observational data. Binary and multinomial logistic treatment models are used when estimating treatment effects to examine whether the extent to which police officers are present in schools impacts problem outcomes. Findings indicated that while the presence of school police officers increased drug-related crimes and out-of-school suspensions for drug crimes regardless of whether they were present in schools for a single year or multiple years, there were deterrent effects observed for violent crimes and incidents of disorder when police officers were present in schools during all school years. Implications for policy and practice are discussed.